EDUKASI PEMANFAATAN BARANG BEKAS UNTUK ANAK-ANAK - Mohammad Hasyim (Asian Journal of Innovation and Entrepreneurship, 2014)
Dusun Sikendil, Banyusidi village, District pakis, Magelang, Central Java. Mostly livelihood society is a farmer and the rest have different professions. Sikendil community organization that has been organized well, including a group of village administrators, group of Rukun Tetangga (RT), group of tahlil, and group of childrens. Which is consist of many children from elementary, junior high school, even in kindergarten. Therefore to improve children's creativity required the development of children through the use of media used goods. This education can increase the level of imagination and gives children the freedom to express ideas or ideas. So recycled things could be used and have a value.